Numerical and Experimental Investigation of Bridge Currents of an Induction Machine Equipped with Bridge Conﬁgured Winding - Sivaramakrishnan Natesan; Karuna Kalita; Venkatesu Samala (International Journal of Electrical and Computer Engineering (IJECE), 2015)
An eccentric rotor motion imbalances the magnetic ﬁeld distribution in the air-gap region. Due to this uneven ﬂux density distribution, a net radial force called Unbalanced Magnetic Pull (UMP) is in action towards the shortest air-gap. This UMP can degrade the machine’s performance. UMP can be controlled by a special kind of winding called Bridge Conﬁgured Winding (BCW). The BCW winding is a single set of winding which is used to produce the torque as well as the controllable force. The main contribution of this paper is to inspect the ﬂow of bridge currents in the bridges when the machine is having rotor eccentricity or unbalance. The bridge currents in the presence of rotor eccentricity with the stator of an Induction machine model has been analyzed by using an Electromagnetic Finite Element (FE) solver called Opera 2D/RM solver (Rotation Motion Analysis). The bridge currents have been measured for two different cases., (i) Induction machine model with zero eccentricity, (ii) Induction machine model with 10% static eccentricity of the air gap. Experimental results are presented for the validation of Opera 2D/RM results. A modiﬁed 37kW Induction machine has been used for this study. A known mass unbalance is introduced in the perforated disc in order to create the unbalance in the system purposefully. The bridge currents have been measured and compared with and without unbalance present in the system. The comparison of measured bridge currents for all the cases are given in the frequency domain.